Les realtions interethniques dans les services éducatifs et sociaux: au delà de l’angélisme et de l’intransigeance, la construction de scénarios inédits - Leclerc, Chantal (Canadian Journal of Counselling and Psychotherapy, 2007)
What social-psychological processes characterize the relation between practitioners and clients from an ethnic minority in a context of a social or educational intervention? The author underlines the heuristic and pragmatic relevance of recognizing the cultural shocks and the psychosocial processes of minority/majority influences which take place in these situations. After the gap between clients' and practitioners' representations of social and educational services is illustrated, the asymmetry of the relationship between social actors is stressed. In this regard, Moscovici's theory (Moscovici, 1985) on social influence brings in an essential contribution to the practice of interethnic counseling.